1976
DOI: 10.1159/000208010
|View full text |Cite
|
Sign up to set email alerts
|

Acute Disseminated Lymphosarcoma with B Cell Markers in a Child

Abstract: A case of a 4-year-old child with disseminated lymphosarcoma with meningeal involvement is described. Immunological investigations of the blast cells in the cerebrospinal fluid were carried out and in most of them Ig determinants and no response to PHA stimulation were found. So the B-dependent nature of these cells was ascertained. This observation is a contribution to the diagnosis of lymphoid malignancies through the evaluation of the immunological nature of the blast cells. The data of the literature are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1977
1977
1996
1996

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The plasma cells, or mature secretory B cells, have inconsistent surface markers, but contain intracytoplasmic Ig (Corte et al, 1976). We and others have found identical variations in the pattern of surface Ig, Fe and C3 receptors in human material such as normal peripheral blood (Habeshaw and Young, 1975), tonsil (Siegel, Grieco and Gupta, 1974), and in lymphomas (Brouet et al, 1975;Dorfman, 1975;Jaffe et al, 1975;Stuart and Habeshaw, 1976;Habeshaw and Stuart, 1975;Moscatelli, Bricarelli and Quartino, 1976). It therefore seems likely that the sequence of phenotype change seen in mature mouse B-lymphoid populations also occurs in man.…”
mentioning
confidence: 53%
“…The plasma cells, or mature secretory B cells, have inconsistent surface markers, but contain intracytoplasmic Ig (Corte et al, 1976). We and others have found identical variations in the pattern of surface Ig, Fe and C3 receptors in human material such as normal peripheral blood (Habeshaw and Young, 1975), tonsil (Siegel, Grieco and Gupta, 1974), and in lymphomas (Brouet et al, 1975;Dorfman, 1975;Jaffe et al, 1975;Stuart and Habeshaw, 1976;Habeshaw and Stuart, 1975;Moscatelli, Bricarelli and Quartino, 1976). It therefore seems likely that the sequence of phenotype change seen in mature mouse B-lymphoid populations also occurs in man.…”
mentioning
confidence: 53%
“…Would the immunologic abnormalities be reversible in young animals whose mothers had been subjected to a chronic nutritional insult before and͞or during gestation? Both in small-for-gestation low-birth-weight infants (26,27) and in animal models of intrauterine undernutrition or zinc deficiency (28,29), the immunologic impairment is profound and long lasting. What is the status of other immunologic mechanisms that play an important role in defense against intracellular pathogens, e.g., CD4…”
mentioning
confidence: 99%
“…Ferguson et al (1974) found in these infants a significant decrease in the number of lymphocytes forming spontaneous rosettes (49.2 % ± 2.0 SD) as compared with normal neonates (65.1 % ± 1.4) and Chandra (1975) found, in their umbilical blood, T--lymphocyte suppression persisting up to the age of 3 months. Moscatelli et al ( 1976) also demonstrated a reduced relative and absolute T -lymphocyte count in the blood of low birthweight neonates (Fig. 65); in some cases they found that it was normalized during the first 3 -4 weeks of life, but in others, as mentioned above, it persisted for several months, indicating that deficient cellular immunity can be of a lasting nature in small-for-dates infants.…”
Section: Cellular Immunitymentioning
confidence: 78%
“…Some studies of cord blood B lymphoyctes with membrane immunoglobulins draw attention to their higher relative number compared with the blood of adults (Papamichail et al 1971, Moscatelli et al 1973 Immunol. In other words, neonates are presumably born with a full complement of this type of peripheral lymphocytes.…”
Section: B Lymphocytes With Surface Membrane Immunoglobulins In the Bmentioning
confidence: 99%
See 1 more Smart Citation